KARAKTERISTIK DINAMIS PERAN GANDA WANITA - Puspa Yusuf, Ria (Jurnal Studi Jender SRIKANDI, 2012)
Woman partsipation consists of tradition and transition roles. The tradition or domestic role includes womwn as a wife, mother and household manager. Meanwhile the transition or public role covers woman as a labor, member of society and development as a whole. Nowadays, the phenomenon in the society is woman tends to work harder to earn money for the family and to express themselves. One indicator of woman role in national development can be seen from an increase in variety of woman job, it does not mean that the woman welfare increase automatically. The woman face discrimation, not only in domestic sector but also in public sector. Therefore, the dynamic characteristic of woman multifunction is important to be learned Kata kunci : Karakteristik dinamis, Peran ganda wanita
Keywords: Peran Ganda Wanita